Thinking Identities - Brah, Avtar. author. aut Link
XI, 225 p.
Keywords: This book brings together research about a diverse range of groups who are rarely analysed together: Welsh, Irish, Jewish, Arab, White, African and Indian. The aim of the book is to critique orthodox explanations in the field, drawing upon the best of 'old' and 'new' theory. Key contemporary questions include: issues about the black-white model of racism; the underplaying of anti-semitism; the need to examine ethnic majorities, as well as whiteness and the reconfiguration of the United Kingdom.